Organizational Ambidexterity: How Small Technology Firms Balance Innovation and Support - Alem Legesse; John Schreuders (Technology Innovation Management Review, 2012)
Many technology entrepreneurs start their companies by focusing on an innovation that creates a market offer to attract their first customers. When the entrepreneur’s firm makes its first sale, the dynamics of the organization change and the entrepreneur faces a new challenge: how can the firm concurrently develop new products and support existing customers? This problem is of great concern to entrepreneurs who own small technology firms and is the subject of this article. In this article, we first address the innovate-versus-support dilemma that small technology firms face early in their lifecycles. Next, we describe the paradigm of the ambidextrous organization. We conclude with a discussion of five mechanisms small firms can use to achieve balance in their quest to concurrently satisfy the need to innovate while fulfilling the demands of existing clients and products.